Antibiotic resistant bacteria in goat meat and hygienic practices among retail stores in Nashville, Tennessee - Owusu, Moses; Basnet, Ashesh; Kilonzo-Nthenge, Agnes (Frontiers in Sustainable Food Systems, 2024)
This study explores into the levels of coliform contamination, prevalence of antibiotic-resistant bacteria, and the hygienic practices in goat meat retail stores. Goat meat from 10 retail stores was analyzed for E. coli, Salmonella, and S. aureus using serological and PCR methods. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Data on hygienic practices were collected through a structured observational questionnaire. Pearson's correlation analysis was also employed to establish the relationship between hygienic practices and coliform loads. The average coliform loads on goat meat ranged between 0.88-5.04 log10 cfu/g. Our results revealed that 52% of examined goat meat was deemed unacceptable (>3.30 log10 CFU/g). The overall level of good meat handling practices among meat handlers in our study was 45.75%. Further, the study establishes a significant correlation between the level of food safety practices and coliform load. Hence, stores with higher hygienic practice scores exhibited lower coliform loads. The prevalence of S. aureus (44%) in goat meat was significantly higher (p < 0.05) as compared to E. coli (29%), and Salmonella spp. (20%). E. coli isolates displayed the highest resistance to penicillin (31.2%), Salmonella spp. to oxytetracycline (13.9%), and S. aureus to ampicillin (29.0%). Resistance was observed across selected antibiotic classes, particularly in beta-lactams and tetracyclines, with penicillin (78.5%) and oxytetracycline (64.5%) exhibiting notable resistance. Cephalosporin resistance was noted, with 48.4% and 33.3% of isolates showing resistance to cephalothin and cefpodoxime, respectively. Bacterial isolates also demonstrated resistance to phenicol antibiotics, including chloramphenicol (9.7%) and florfenicol (16.1%), respectively. Approximately 44.1% of bacterial isolates displayed multidrug resistance and MAR index ranged from 0.25 to 0.75. The study's findings reveal heightened levels of coliform contamination, the presence of pathogenic and multidrug-resistant bacteria in goat meat, and suboptimal meat handling practices in retail stores. The significance of improving food safety practices in retail settings is emphasized to ensure the safety of goat meat, a matter of increasing importance due to its growing demand globally.